2021
DOI: 10.3390/biom11050729
|View full text |Cite
|
Sign up to set email alerts
|

Phototheranostics Using Erythrocyte-Based Particles

Abstract: There has been a recent increase in the development of delivery systems based on red blood cells (RBCs) for light-mediated imaging and therapeutic applications. These constructs are able to take advantage of the immune evasion properties of the RBC, while the addition of an optical cargo allows the particles to be activated by light for a number of promising applications. Here, we review some of the common fabrication methods to engineer these constructs. We also present some of the current light-based applica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 137 publications
(226 reference statements)
1
13
0
Order By: Relevance
“…A slight increase is noted after the penultimate wash, but this is due to the recurrences that remain prior to the addition of PBS solution. The color change in the solution from red to pink suggests that hemoglobin is released from the interior of the red blood cells, which when it clarifies is an indication of hemoglobin elimination or the presence of cell membranes (erythrocyte ghost), as previously reported [ 23 , 56 , 57 , 58 ]. As hemoglobin is eliminated during the lysis process, the Fe content decreases until finally disappearing when the process is completed.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…A slight increase is noted after the penultimate wash, but this is due to the recurrences that remain prior to the addition of PBS solution. The color change in the solution from red to pink suggests that hemoglobin is released from the interior of the red blood cells, which when it clarifies is an indication of hemoglobin elimination or the presence of cell membranes (erythrocyte ghost), as previously reported [ 23 , 56 , 57 , 58 ]. As hemoglobin is eliminated during the lysis process, the Fe content decreases until finally disappearing when the process is completed.…”
Section: Discussionsupporting
confidence: 57%
“…The integration of fluorescent nanoparticles into biological structures with the capacity to host and release a drug improves their performance in biomedical applications [ 21 , 22 ]. Red blood cells, also known as erythrocytes, have been used as biological carriers due their biophysical properties [ 23 , 24 , 25 , 26 ]; these are enucleated cells without organelles with a diameter of 8–9 µm; they are flexible due to the properties of the plasma membrane and can circulate freely in the human body. A variant of these red blood cells is the erythrocyte ghost [ 27 , 28 , 29 , 30 ], which is a membranous structure free of hemoglobin that originates when the erythrocyte is exposed to a hypotonic medium, causing cell cytolysis and releasing hemoglobin into the medium (hemolysis), giving it the capacity to encapsulate a drug.…”
Section: Introductionmentioning
confidence: 99%
“…7 However, polyelectrolytes are exogenous substances that are easily removed from the body by the immune system. Therefore, the endogenous material erythrocyte membrane (RBC membrane) [25][26][27][28][29] is used in this study, which can prolong the retention time of the carrier in the blood, thus improving the therapeutic effect. [30][31][32] The RBC membrane is a natural long cycle carrier with good biocompatibility.…”
Section: Introductionmentioning
confidence: 99%
“…The functionalities of the cell membrane-cloaked nanoparticles are largely influenced by the inherent properties of the source cells. In the following section, we introduce source cell types for cell membranes and their unique features helpful for targeted drug delivery, phototherapy, immune modulation, and theragnostic [23][24][25][26][27][28][29].…”
Section: Cell Membrane Cloaking Technologymentioning
confidence: 99%
“…RBCs are disciform with a hollow center, allowing resistance to osmotic pressure or external shock and flexibility to pass through the capillary. RBC membranes were extensively used for modifying nanoparticles due to their ability to avoid the immune system and achieve long-term circulation [2,25,[27][28][29][30][31]. For example, Hu et al [32] reported that RBC membrane-coated nanoparticles had significantly longer circulation time as compared to that of bare nanoparticles or RBC membrane vesicles.…”
Section: Natural Cell Membranes and Their Unique Featuresmentioning
confidence: 99%